A method for preparing water-based coating for antistatic treatment of flexible PVC material

Through the composite of polyacrylate and polyurethane and the electrostatic adsorption of modified graphene, the shortcomings of aqueous coatings in terms of flexibility, conductivity and conductivity stability are solved, and high-performance anti-static coatings are achieved.

CN119552550BActive Publication Date: 2025-04-18CHENGDU VISION COMPOSITE MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510115685.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-18
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

Existing water-based coatings need to improve flexibility, conductivity and conductivity stability, especially during frequent water permeability and drying, the conductive material is prone to migration and loss, resulting in a decrease in conductivity stability.

Method used

By combining polyacrylate with polyurethane, a network structure with interpenetrating molecular chain crosslinking is formed, the flexibility and adhesion of the material are increased, and the electrostatic adsorption of modified graphene and composite polyurethane is formed to form a stable dispersion system to improve conductivity and stability.

Benefits of technology

It significantly improves the flexibility, conductivity and conductivity stability of water-based coatings, prevents the migration of conductive materials, and maintains the overall performance of the materials. It is suitable for underground antistatic applications of coal mines.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing a water-based coating for antistatic treatment of a flexible PVC material, belongs to the technical field of antistatic coating processing, and is used to solve the technical problem that the flexibility, conductivity and conductive stability of a water-based coating film in the prior art need to be further improved. The invention comprises the following steps: adding polyacrylate to a polyurethane emulsion and stirring, adding a sodium hydroxide solution to a reaction system, adjusting the pH value of the system to 8-9, raising the temperature of the reaction system to 70-80 DEG C, keeping the temperature and stirring for 90-120 minutes, and post-treating to obtain a composite polyurethane. The invention comprises the following steps: modifying graphene oxide and mixing it with a composite polyurethane material reinforced with polyacrylate, which not only effectively improves the antistatic performance, flexibility and adhesion of the water-based coating, but also has good water washing resistance and migration performance, and improves its conductive stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of antistatic coating processing, and in particular to a method for preparing a water-based coating for antistatic treatment of flexible PVC materials. Background Art

[0002] In coal mines, spark discharge of static electricity has become one of the sources of fire. Explosions or fires caused by static electricity discharge occur from time to time. It is very important to eliminate the large accumulation of charges and prevent static electricity sparks underground. Antistatic fabrics in coal mines are usually PVC materials. In order to reduce the resistance value of the material and improve the antistatic performance of the material, the material is usually treated by adding antistatic agents or solvent-based surface treatment agents. However, due to the problems of the material itself, adding antistatic materials makes the processing process difficult and the half-life of the static value is short. Solvent-based surface treatment agents have defects such as being environmentally unfriendly, flammable, and explosive.

[0003] Water-based paint is a product with little environmental pollution and is safe. By adding specific antistatic agents, such as cellulose acetate, and then mixing with polyvinyl alcohol solution, fillers, coupling agents, etc., a coating material with antistatic properties is prepared. In addition, PVC antistatic cloth with high antistatic properties is prepared by compounding nanomaterials such as graphene and carbon nanotubes. However, inorganic conductive materials such as graphene are added to water-based paint, which is difficult to disperse evenly in water-based polyester, resulting in its conductive properties needing to be further improved. During use, PVC antistatic cloth for coal mines will experience frequent water penetration and drying processes. The conductive material on the coating is easily migrated and lost, resulting in a decrease in its conductive stability. In addition, the coating will also be bent and damaged during use, resulting in damage to its overall structure.

[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a water-based coating for antistatic treatment of flexible PVC materials, so as to solve the technical problem in the prior art that the flexibility, conductivity and conductive stability of the water-based coating film need to be further improved.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for preparing a water-based coating for antistatic treatment of a flexible PVC material comprises the following steps:

[0008] S1. Add polyacrylate to polyurethane emulsion and stir, add sodium hydroxide solution to the reaction system, adjust the pH value of the system to 8-9, increase the temperature of the reaction system to 70-80°C, keep warm and stir for 90-120 minutes, and post-treat to obtain composite polyurethane;

[0009] The synthesis reaction principles of composite polyurethane include:

[0010] ;

[0011] ;

[0012] ;

[0013] The synthetic reaction mechanism of composite polyurethane is:

[0014] During the reaction, sodium hydroxide provides an alkaline environment, and the carboxyl groups on the polyacrylate molecules react with sodium hydroxide to form sodium carboxylate. At the same time, sodium hydroxide promotes the ring-opening condensation between the epoxy group and the imino group or hydroxyl group on the polyurethane molecule, and the polyacrylate and the polyurethane are compounded in the form of chemical bonding to prepare a composite polyurethane.

[0015] S2, adding the composite polyurethane, modified graphene and emulsion into a high-speed disperser, emulsifying and dispersing for 20-30 minutes to obtain a water-based coating premix;

[0016] S3. Cool the water-based paint premix to 10-15° C., add KH-560 and additives to the water-based paint premix, and stir for 3-5 minutes to obtain a water-based paint.

[0017] Furthermore, in step S1, the usage ratio of the polyacrylate and the polyurethane emulsion is 1g:10mL, the concentration of the sodium hydroxide solution is 1-2mol / L, and the post-treatment includes, after the reaction is completed, the reaction system is kept warm at 70-80°C, the solvent is evaporated under reduced pressure, ethyl acetate is added to the reaction system, stirred until the system is dissolved, the reaction system is cooled to room temperature, filtered, and the filtrate is transferred to a rotary evaporator with a water bath temperature of 60-70°C, and the solvent is evaporated under reduced pressure to obtain a composite polyurethane.

[0018] Furthermore, in step S2, the amount ratio of the composite polyurethane, modified graphene and emulsion is 5g:1g:20mL, the emulsion is composed of sodium dodecylbenzene sulfonate, Tween-80, sodium hydroxide and deionized water in a ratio of 3g:2g:1g:100mL, and the rotation speed of the high-speed disperser is 1000-1200r / min.

[0019] Furthermore, in step S3, the amount ratio of the water-based paint premix, KH-560 and the additive is 100mL:3g:8g, and the additive consists of a thickener, an anti-settling agent, an anti-mildew agent, and a leveling agent in a weight ratio of 6:2:3:2. The thickener is hydroxyethyl cellulose, the anti-settling agent is fumed silica, the anti-mildew agent is 2-(4-thiazolyl)benzimidazole, and the leveling agent is an acrylic leveling agent.

[0020] Furthermore, the preparation method of polyacrylate is as follows: under the protection of inert gas, methyl methacrylate, butyl acrylate, acrylic acid, 1,2-epoxy-7-octene and n-butanol are mixed and stirred, the temperature of the reaction system is increased to 70-80°C, an initiator solution is added dropwise to the reaction system, the reaction is kept warm for 6-7 hours, and post-processed to obtain polyacrylate.

[0021] The synthetic reaction formula of polyacrylate is:

[0022] ;

[0023] The synthetic reaction mechanism of polyacrylate is:

[0024] During the reaction, under the action of initiator and high temperature, methyl methacrylate, butyl acrylate, acrylic acid and 1,2-epoxy-7-octene undergo free radical polymerization to generate polyacrylate modified with epoxy and carboxyl groups.

[0025] Furthermore, the dosage ratio of the methyl methacrylate, butyl acrylate, acrylic acid, 1,2-epoxy-7-octene, n-butanol and initiator solution is 5g:3g:3g:2g:50mL:10mL, the initiator solution is composed of azobisisobutyronitrile and n-butanol at a ratio of 1g:20mL, and the post-treatment includes: after the reaction is completed, the reaction system is kept at 70-80°C, and the low-boiling substances are removed under reduced pressure to obtain polyacrylate.

[0026] Furthermore, the preparation method of the polyurethane emulsion is as follows: under the protection of inert gas, polytetramethylene glycol, trimethylolpropane, hydroxy silicone oil and a catalyst are mixed and stirred, the temperature of the reaction system is increased to 70-80°C, isophorone diisocyanate is added dropwise to the reaction system, the reaction is kept warm for 2-3 hours, 2,2-dimethylolpropionic acid is added to the reaction system, the reaction is kept warm for 2-3 hours, triethylamine is added to the reaction system, the pH of the system is adjusted to 7, deionized water is added to the reaction system, emulsified and dispersed, and a polyurethane emulsion is obtained.

[0027] The synthetic reaction formula of polyurethane emulsion is:

[0028] ;

[0029] Where:

[0030] ;

[0031] .

[0032] The synthetic reaction mechanism of polyurethane emulsion is:

[0033] During the reaction, hydroxyl groups on the molecules of polytetramethylene glycol, trimethylolpropane and hydroxy silicone oil react with isocyanate groups on isophorone diisocyanate molecules to form a polyurethane prepolymer with interpenetrating cross-linking of molecular chains. 2,2-dimethylolpropionic acid is used as a chain extender, and the hydroxyl groups on its molecules further react with the polyurethane prepolymer. By controlling the molar amounts of isocyanate groups and hydroxyl groups during the reaction, carboxyl modification is formed on the polyurethane molecular chain. The pH of the system is adjusted to neutral by triethylamine, and the carboxyl group reacts with triethylamine to form a carboxylate, which promotes its uniform dispersion in an aqueous solution to prepare a polyurethane emulsion.

[0034] Furthermore, the dosage ratio of the polytetramethylene ether diol, trimethylolpropane, hydroxy silicone oil, catalyst and deionized water is 5g:1g:3g:0.1g:30mL, the isophorone diisocyanate is calculated according to NOH:NNCO=1mol:1.1mol in the reaction system, and the molar amount of the 2,2-dihydroxymethylpropionic acid is 0.05 times the molar amount of isophorone diisocyanate.

[0035] Further, the modified graphene is processed by the following steps:

[0036] A1. Under the protection of inert gas, graphene oxide and N,N-dimethylformamide are mixed, ultrasonically dispersed at room temperature for 30-50 minutes, N,N'-dicyclohexylcarbodiimide is added to the reaction system, and ultrasonication is carried out for 20-30 minutes. The temperature of the reaction system is increased to 65-75°C, N,N-dimethylethylenediamine is added to the reaction system, and the reaction is carried out for 20-22 hours. After post-treatment, a modified graphene precursor is obtained;

[0037] A2. The modified graphene precursor and dimethyl sulfoxide are mixed, and ultrasonic dispersion is performed for 40-60 minutes. The temperature of the reaction system is increased to 60-70° C., butane bromide is added to the reaction system, and the reaction is kept warm for 8-10 hours. After post-treatment, the modified graphene is obtained.

[0038] The synthetic reaction formula of modified graphene is:

[0039] ;

[0040] Where: It is graphene oxide.

[0041] The synthetic reaction mechanism of modified graphene is:

[0042] During the reaction, dicyclohexylcarbodiimide catalyzes the condensation of carboxyl groups on graphene oxide molecules with amino groups on N,N-dimethylethylenediamine molecules to form amide bonds, thereby forming tertiary amino group modifications on the graphene oxide molecules. Under high temperature conditions, the bromine atoms on the bromobutane molecules undergo substitution reactions with the tertiary amino groups to form quaternary ammonium salt structures, thereby preparing modified graphene with quaternary ammonium salt modifications.

[0043] Further, in step A1, the amount ratio of graphene oxide, N,N-dimethylformamide, N,N'-dicyclohexylcarboximide and N,N-dimethylethylenediamine is 1g:200mL:1.2g:3g, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, centrifuged, the bottom solid is washed with N,N-dimethylformamide and deionized water for 3 times and then dried, and the filter cake is transferred to a freeze dryer at a temperature of -30°C and freeze-dried to Constant weight to obtain a modified graphene precursor; in step A2, the amount ratio of the modified graphene precursor, dimethyl sulfoxide and butyl bromide is 1g:100mL:4g, and the post-treatment includes: after the reaction is completed, the temperature of the reaction system is lowered to room temperature, anhydrous ethanol is added to the reaction system, stirred for 30-50min, centrifuged, the solid is washed 3 times with deionized water and then dried, and the filter cake is transferred to a freeze dryer at a temperature of -30°C and freeze-dried to constant weight to obtain modified graphene.

[0044] The present invention has the following beneficial effects:

[0045] 1. The water-based coating for antistatic treatment of flexible PVC material of the present invention forms a network structure with interpenetrating crosslinking of molecular chains by compounding polyacrylate and polyurethane with good flexibility, thereby increasing the flexibility of the composite polyurethane material. Meanwhile, the flexibility of the composite polyurethane molecular chain also helps the paint film to better adapt to the tiny concave-convex of the PVC surface and enhance the adhesion. The carboxylates on the molecular chains of polyacrylate and polyurethane can enhance the conductivity of the paint film, and the carboxylates on the molecular chains are ionized in aqueous solution and exhibit negative charge, which forms electrostatic adsorption with the positively charged modified graphene, promotes the close combination between the modified graphene and the composite polyurethane, increases the compatibility between the material molecules, forms a stable dispersion system in the water-based coating, further increases the conductive performance and molecular stability of the coating, prevents the migration of organic components on the material molecules, and maintains the conductive stability of the material.

[0046] 2. The water-based coating for antistatic treatment of flexible PVC materials of the present invention is prepared by free radical addition reaction of methyl methacrylate, butyl acrylate, acrylic acid and 1,2-epoxy-7-octene to obtain polyacrylate modified with carboxyl and epoxy groups. The butyl ester side chains on the polyacrylate molecules can increase the distance between polymer molecular chains and reduce the interaction force between molecular chains, so that the polyacrylate exhibits good flexibility and elasticity. By introducing polytetramethylene ether glycol and hydroxy silicone oil blocks into the polyurethane molecular chain, polytetramethylene ether glycol is a long-chain glycol with excellent flexibility, thereby giving the polyurethane good elasticity and flexibility, and the hydroxy silicone oil has Lower surface energy and good lubricity increase the mobility of polyurethane chain segments, further improving the surface properties and flexibility of polyurethane materials. 2,2-Dihydroxymethylpropionic acid is used as a chain extender to increase the length of the molecular chain while introducing carboxyl groups into the polyurethane molecular chain. In an alkaline environment, the carboxyl groups form sodium carboxylate salts, which increase the conductivity of the polyurethane material. The interpenetrating network cross-linking structure between polyurethane and polyacrylate molecules enhances the interaction force between polymer molecular chains, thereby improving the cohesion of the material. The increase in cohesion helps the material maintain its integrity when subjected to external forces, making it less likely to fall off or peel off, and increases the interfacial bonding force, thereby improving the material's adhesion to the substrate.

[0047] 3. The water-based coating for antistatic treatment of flexible PVC material of the present invention is prepared by modifying graphene and modifying quaternary ammonium salt on the graphene molecule. In an aqueous environment, electrostatic adsorption is formed between the modified graphene showing positive charge and the composite polyurethane showing negative charge, so that the modified graphene can be uniformly dispersed and mixed in the composite polyurethane. The modified graphene itself has good electrical conductivity. By increasing its dispersibility in the composite polyurethane, the coating material shows good electrical conductivity. The two-dimensional structure of the modified graphene enables it to disperse stress when subjected to external force, preventing the paint film from being broken due to excessive local stress, and further enhancing the flexibility of the paint film. KH-560 is added to the premix under a low temperature environment to extend the time for hydrolysis of siloxane bonds in the KH-560 molecule. When the coating is applied and dried, the weakly alkaline environment can promote the ring-opening condensation of epoxy groups with functional groups such as hydroxyl groups or imino groups, and the silanol groups generated by the hydrolysis of the siloxane bonds can bond to the surface of the PVC substrate, further enhancing the adhesion performance of the coating. DETAILED DESCRIPTION

[0048] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] In this application, the molecular weight of polytetramethylene glycol is 1000±50, the viscosity at 40°C is 270cp, and the hydroxyl number is 106.1-118.1mgKOH / g; the model of hydroxy silicone oil is JHG-805-2, and the viscosity (25°C) is 30mm 2 / s, hydroxyl content is 6-8%, relative density is 0.92; the model of acrylic leveling agent is BYK-358N.

[0050] Embodiment 1:

[0051] This embodiment provides a method for preparing a water-based coating for antistatic treatment of a flexible PVC material, comprising the following steps:

[0052] S1. Preparation of polyacrylate:

[0053] Azobisisobutyronitrile and n-butanol were mixed evenly at a ratio of 1 g:20 mL to obtain an initiator solution for later use;

[0054] Weigh: 50 g of methyl methacrylate, 30 g of butyl acrylate, 30 g of acrylic acid, 20 g of 1,2-epoxy-7-octene and 500 mL of n-butanol, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 70°C, add 100 mL of initiator solution dropwise into the three-necked flask, and keep warm for 6 hours. After the reaction is completed, keep the three-necked flask at 70°C, reduce the pressure and remove low-boiling substances to obtain polyacrylate.

[0055] S2, preparing polyurethane emulsion:

[0056] Weigh: 50g of polytetramethylene glycol, 10g of trimethylolpropane, 30g of hydroxy silicone oil, and 1g of catalyst dibutyltin dilaurate, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 70°C, calculate the amount of isophorone diisocyanate added according to the molar ratio of hydroxyl to isocyanate in the reaction system of 1:1.1, and add it dropwise into the three-necked flask, keep warm and react for 2h, calculate the amount of 2,2-dimethylolpropionic acid added according to 0.05 times the molar amount of isophorone diisocyanate, and add it into the three-necked flask, keep warm and react for 2h, add triethylamine into the three-necked flask, adjust the pH of the system to 7, add deionized water into the reaction system, emulsify and disperse, and obtain a polyurethane emulsion.

[0057] S3, preparation of composite polyurethane:

[0058] Weigh: 50 g of polyacrylate and 500 mL of polyurethane emulsion are added to a three-necked flask and stirred. 0.3 mol / L sodium hydroxide solution is added to the three-necked flask to adjust the pH of the system to 8. The temperature of the three-necked flask is increased to 70°C, and the reaction is kept warm for 90 minutes. The three-necked flask is kept warm at 70°C, and the solvent is evaporated under reduced pressure. 500 mL of ethyl acetate is added to the reaction system, and the system is stirred until it is dissolved. The three-necked flask is cooled to room temperature, filtered, and the filtrate is transferred to a rotary evaporator with a water bath temperature of 60°C, and the solvent is evaporated under reduced pressure to obtain a composite polyurethane.

[0059] S4. Preparation of modified graphene:

[0060] Weigh: 5 g of graphene oxide and 1000 mL of N,N-dimethylformamide are added to a three-necked flask protected by nitrogen, and ultrasonic dispersion is performed at room temperature for 30 min. 6 g of N,N'-dicyclohexylcarbodiimide is added to the three-necked flask, and the mixture is kept warm and ultrasonicated for 20 min. The three-necked flask is transferred to an iron stand with mechanical stirring, and the temperature of the three-necked flask is increased to 65°C. 15 g of N,N-dimethylethylenediamine is added to the three-necked flask, and the mixture is kept warm and reacted for 20 h. The temperature of the three-necked flask is lowered to room temperature, and the mixture is centrifuged. The solid at the bottom is washed three times with N,N-dimethylformamide and deionized water, respectively, and then dried. The filter cake is transferred to a freeze dryer at a temperature of -30°C and freeze-dried to a constant weight to obtain a modified graphene precursor.

[0061] Weigh: 5 g of modified graphene precursor and 500 mL of dimethyl sulfoxide are added to a three-necked flask and ultrasonically dispersed for 40 minutes. The three-necked flask is transferred to an iron stand with mechanical stirring. The temperature of the three-necked flask is increased to 60°C. 20 g of bromobutyl is added to the three-necked flask. The reaction is kept warm for 8 hours. The temperature of the three-necked flask is lowered to room temperature. 1000 mL of anhydrous ethanol is added to the three-necked flask. The mixture is stirred for 30 minutes and centrifuged. The solid is washed three times with deionized water and then dried. The filter cake is transferred to a freeze dryer at -30°C and freeze-dried to constant weight to obtain modified graphene.

[0062] S5. Preparation of water-based coating:

[0063] Sodium dodecylbenzene sulfonate, Tween-80, sodium hydroxide and deionized water were mixed uniformly in the amount ratio of 3g:2g:1g:100mL to obtain an emulsion for standby use; the emulsion was prepared by

[0064] The composite polyurethane, modified graphene and emulsion were mixed at a ratio of 5 g: 1 g: 20 mL and added into a high-speed disperser. The speed of the high-speed disperser was set to 1000 r / min. The emulsification and dispersion were performed for 30 minutes to obtain a water-based coating premix.

[0065] The thickener hydroxyethyl cellulose, the anti-settling agent fumed silica, the anti-mildew agent 2-(4-thiazolyl)benzimidazole, and the acrylic ester leveling agent are mixed uniformly in a weight ratio of 6:2:3:2 to obtain an additive auxiliary agent for standby use;

[0066] Weigh: 1000 mL of water-based paint premix is ​​added into a beaker. The temperature of the beaker is cooled to 10°C. Under stirring, 30 g of KH-560 and 80 g of additive are added into the beaker. The mixture is stirred for 5 minutes under heat preservation to obtain a water-based paint.

[0067] Embodiment 2:

[0068] This embodiment provides a method for preparing a water-based coating for antistatic treatment of a flexible PVC material, comprising the following steps:

[0069] S1. Preparation of polyacrylate:

[0070] Azobisisobutyronitrile and n-butanol were mixed evenly at a ratio of 1 g:20 mL to obtain an initiator solution for later use;

[0071] Weigh: 50 g of methyl methacrylate, 30 g of butyl acrylate, 30 g of acrylic acid, 20 g of 1,2-epoxy-7-octene and 500 mL of n-butanol, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 75°C, add 100 mL of initiator solution dropwise into the three-necked flask, keep warm and react for 6.5 hours, after the reaction is completed, keep the three-necked flask at 75°C, reduce the pressure and remove low boiling points to obtain polyacrylate.

[0072] S2, preparing polyurethane emulsion:

[0073] Weigh: 50g of polytetramethylene glycol, 10g of trimethylolpropane, 30g of hydroxy silicone oil, and 1g of catalyst dibutyltin dilaurate, add them to a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 75°C, calculate the amount of isophorone diisocyanate added according to the molar ratio of hydroxyl to isocyanate in the reaction system of 1:1.1, and add it dropwise to the three-necked flask, keep warm and react for 2.5h, calculate the amount of 2,2-dihydroxymethylpropionic acid added according to 0.05 times the molar amount of isophorone diisocyanate, and add it to the three-necked flask, keep warm and react for 2.5h, add triethylamine to the three-necked flask, adjust the pH of the system to 7, add deionized water to the reaction system, emulsify and disperse, and obtain a polyurethane emulsion.

[0074] S3. Preparation of composite polyurethane:

[0075] Weigh: 50 g of polyacrylate and 500 mL of polyurethane emulsion are added to a three-necked flask and stirred. 0.4 mol / L sodium hydroxide solution is added to the three-necked flask to adjust the system pH to 8.5. The temperature of the three-necked flask is raised to 75°C, and the reaction is kept warm for 105 minutes. The three-necked flask is kept warm at 75°C, and the solvent is evaporated under reduced pressure. 500 mL of ethyl acetate is added to the reaction system, and the system is stirred until it is dissolved. The three-necked flask is cooled to room temperature, filtered, and the filtrate is transferred to a rotary evaporator with a water bath temperature of 65°C, and the solvent is evaporated under reduced pressure to obtain a composite polyurethane.

[0076] S4. Preparation of modified graphene:

[0077] Weigh: 5 g of graphene oxide and 1000 mL of N,N-dimethylformamide are added to a three-necked flask protected by nitrogen, and ultrasonically dispersed at room temperature for 40 min. 6 g of N,N'-dicyclohexylcarbodiimide is added to the three-necked flask, and the mixture is kept warm and ultrasonicated for 25 min. The three-necked flask is transferred to an iron stand with mechanical stirring, and the temperature of the three-necked flask is increased to 70°C. 15 g of N,N-dimethylethylenediamine is added to the three-necked flask, and the mixture is kept warm and reacted for 21 h. The temperature of the three-necked flask is lowered to room temperature, and the mixture is centrifuged. The solid at the bottom is washed three times with N,N-dimethylformamide and deionized water, respectively, and then dried. The filter cake is transferred to a freeze dryer at a temperature of -30°C and freeze-dried to a constant weight to obtain a modified graphene precursor.

[0078] Weigh: 5 g of modified graphene precursor and 500 mL of dimethyl sulfoxide are added to a three-necked flask and ultrasonically dispersed for 50 min. The three-necked flask is transferred to an iron stand with mechanical stirring. The temperature of the three-necked flask is increased to 65°C. 20 g of bromobutyl is added to the three-necked flask and the reaction is kept warm for 9 h. The temperature of the three-necked flask is lowered to room temperature. 1000 mL of anhydrous ethanol is added to the three-necked flask, stirred for 40 min, and centrifuged. The solid is washed 3 times with deionized water and then dried. The filter cake is transferred to a freeze dryer at -30°C and freeze-dried to constant weight to obtain modified graphene.

[0079] S5. Preparation of water-based coating:

[0080] Sodium dodecylbenzene sulfonate, Tween-80, sodium hydroxide and deionized water were mixed uniformly in a dosage ratio of 3g:2g:1g:100mL to obtain an emulsion for later use;

[0081] The composite polyurethane, modified graphene and emulsion were mixed at a ratio of 5 g: 1 g: 20 mL and added into a high-speed disperser. The speed of the high-speed disperser was set to 1100 r / min. The emulsification and dispersion were performed for 25 min to obtain a water-based coating premix.

[0082] The thickener hydroxyethyl cellulose, the anti-settling agent fumed silica, the anti-mildew agent 2-(4-thiazolyl)benzimidazole, and the acrylic ester leveling agent are mixed uniformly in a weight ratio of 6:2:3:2 to obtain an additive auxiliary agent for standby use;

[0083] Weigh: 1000 mL of water-based paint premix is ​​added into a beaker. The temperature of the beaker is cooled to 13°C. Under stirring, 30 g of KH-560 and 80 g of additive are added into the beaker. The mixture is stirred for 4 minutes under heat preservation to obtain a water-based paint.

[0084] Embodiment 3:

[0085] This embodiment provides a method for preparing a water-based coating for antistatic treatment of a flexible PVC material, comprising the following steps:

[0086] S1. Preparation of polyacrylate:

[0087] Azobisisobutyronitrile and n-butanol were mixed evenly at a ratio of 1 g:20 mL to obtain an initiator solution for later use;

[0088] Weigh: 50 g of methyl methacrylate, 30 g of butyl acrylate, 30 g of acrylic acid, 20 g of 1,2-epoxy-7-octene and 500 mL of n-butanol, add into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 80°C, add 100 mL of initiator solution dropwise into the three-necked flask, and keep warm for 7 hours. After the reaction is completed, keep the three-necked flask at 80°C, reduce the pressure and remove low-boiling substances to obtain polyacrylate.

[0089] S2, preparing polyurethane emulsion:

[0090] Weigh: 50g of polytetramethylene glycol, 10g of trimethylolpropane, 30g of hydroxy silicone oil, and 1g of catalyst dibutyltin dilaurate, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to 80°C, calculate the amount of isophorone diisocyanate added according to the molar ratio of hydroxyl to isocyanate in the reaction system of 1:1.1, and add it dropwise into the three-necked flask, keep warm and react for 3h, calculate the amount of 2,2-dihydroxymethylpropionic acid added according to 0.05 times the molar amount of isophorone diisocyanate, and add it into the three-necked flask, keep warm and react for 3h, add triethylamine into the three-necked flask, adjust the pH of the system to 7, add deionized water into the reaction system, emulsify and disperse, and obtain a polyurethane emulsion.

[0091] S3. Preparation of composite polyurethane:

[0092] Weigh: 50 g of polyacrylate and 500 mL of polyurethane emulsion are added to a three-necked flask and stirred. 0.5 mol / L sodium hydroxide solution is added to the three-necked flask to adjust the system pH to 9. The temperature of the three-necked flask is increased to 80°C, and the reaction is kept warm for 120 minutes. The three-necked flask is kept warm at 80°C, and the solvent is evaporated under reduced pressure. 500 mL of ethyl acetate is added to the reaction system, and the system is stirred until it is dissolved. The three-necked flask is cooled to room temperature, filtered, and the filtrate is transferred to a rotary evaporator with a water bath temperature of 70°C, and the solvent is evaporated under reduced pressure to obtain a composite polyurethane.

[0093] S4. Preparation of modified graphene:

[0094] Weigh: 5 g of graphene oxide and 1000 mL of N,N-dimethylformamide are added to a three-necked flask protected by nitrogen, and ultrasonic dispersion is performed at room temperature for 50 min. 6 g of N,N'-dicyclohexylcarbodiimide is added to the three-necked flask, and the mixture is kept warm and ultrasonicated for 30 min. The three-necked flask is transferred to an iron stand with mechanical stirring, and the temperature of the three-necked flask is increased to 75°C. 15 g of N,N-dimethylethylenediamine is added to the three-necked flask, and the mixture is kept warm and reacted for 22 h. The temperature of the three-necked flask is lowered to room temperature, and the mixture is centrifuged. The solid at the bottom is washed three times with N,N-dimethylformamide and deionized water, respectively, and then dried. The filter cake is transferred to a freeze dryer at a temperature of -30°C and freeze-dried to a constant weight to obtain a modified graphene precursor.

[0095] Weigh: 5 g of modified graphene precursor and 500 mL of dimethyl sulfoxide are added to a three-necked flask and ultrasonically dispersed for 60 min. The three-necked flask is transferred to an iron stand with mechanical stirring. The temperature of the three-necked flask is increased to 70°C. 20 g of bromobutyl is added to the three-necked flask. The reaction is kept warm for 10 h. The temperature of the three-necked flask is lowered to room temperature. 1000 mL of anhydrous ethanol is added to the three-necked flask. The mixture is stirred for 50 min and centrifuged. The solid is washed three times with deionized water and then dried. The filter cake is transferred to a freeze dryer at -30°C and freeze-dried to constant weight to obtain modified graphene.

[0096] S5. Preparation of water-based coating:

[0097] Sodium dodecylbenzene sulfonate, Tween-80, sodium hydroxide and deionized water were mixed uniformly in a dosage ratio of 3g:2g:1g:100mL to obtain an emulsion for later use;

[0098] The composite polyurethane, modified graphene and emulsion were mixed at a ratio of 5 g: 1 g: 20 mL and added into a high-speed disperser. The speed of the high-speed disperser was set to 1200 r / min. The emulsification and dispersion were performed for 20 min to obtain a water-based coating premix.

[0099] The thickener hydroxyethyl cellulose, the anti-settling agent fumed silica, the anti-mildew agent 2-(4-thiazolyl)benzimidazole, and the acrylic ester leveling agent are mixed uniformly in a weight ratio of 6:2:3:2 to obtain an additive auxiliary agent for standby use;

[0100] Weigh: 1000 mL of water-based paint premix is ​​added into a beaker. The temperature of the beaker is cooled to 15°C. Under stirring, 30 g of KH-560 and 80 g of additive are added into the beaker. The mixture is stirred for 3 minutes under heat preservation to obtain a water-based paint.

[0101] Comparative Example 1:

[0102] The difference between this comparative example and Example 3 is that in step S1, 1,2-epoxy-7-octene is not added.

[0103] Comparative Example 2:

[0104] The difference between this comparative example and Example 3 is that in step S2, 2,2-dihydroxymethylpropionic acid is replaced by 1,3-propylene glycol in an equal molar amount.

[0105] Comparative Example 3:

[0106] The difference between this comparative example and Example 3 is that step S4 is eliminated, and the modified graphene in step S5 is replaced by the graphene oxide in step S4.

[0107] Comparative Example 4:

[0108] The difference between this comparative example and Example 3 is that KH-560 is not added in step S5.

[0109] Performance Test:

[0110] The surface resistance of the water-based coatings prepared in Examples 1-3 and Comparative Examples 1-4 was tested on PVC fabrics after coating and forming according to the standard HG / T 3331-2012 "Determination of volume resistivity and surface resistivity of insulating paint films" before and after washing 100 times;

[0111] Referring to the standard GB / T 1731-2020 "Determination of Flexibility of Paint Film and Putty Film", the water-based coatings prepared in Examples 1-3 and Comparative Examples 1-4 were coated on the PVC fabric and passed through a shaft with the smallest diameter;

[0112] The adhesion grade of the paint film after the water-based coatings prepared in Test Examples 1-3 and Comparative Examples 1-4 were coated on the PVC fabric was determined with reference to the standard GB / T 9286-2021 "Scratch test for paints and varnishes";

[0113] The specific test results are shown in Table 1 below.

[0114] Table 1-Performance test data of the sample:

[0115] ;

[0116] Data Analysis:

[0117] Comparative analysis of the data in Table 1 above shows that after the water-based coating prepared by the present invention is applied to modify the PVC fabric, its surface resistance is reduced to 3.03×10 6 Ω, which is much lower than the requirement of less than 3×10 8 The standard of Ω is achieved, so that static electricity is not generated, and the paint film can pass the flexibility test of the shaft rod 6, the adhesion level reaches level 0, and after washing with water 100 times, the surface resistance growth rate is only 4%. All performance test data are better than those of the comparative example, indicating that the present invention not only effectively improves the antistatic performance, flexibility and adhesion of the water-based coating by modifying the graphene oxide and mixing it with the composite polyurethane material reinforced by polyacrylate, but also improves its water washing resistance and migration performance.

[0118] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

[0119] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0120] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a water-based coating for antistatic treatment of flexible PVC materials, characterized in that: The following steps are involved: S1. Add polyacrylate to polyurethane emulsion and stir, add sodium hydroxide solution to the reaction system, adjust the pH value of the system to 8-9, increase the temperature of the reaction system to 70-80°C, keep warm and stir for 90-120 minutes, and post-treat to obtain composite polyurethane; The preparation method of polyacrylate is as follows: under the protection of inert gas, methyl methacrylate, butyl acrylate, acrylic acid, 1,2-epoxy-7-octene and n-butanol are mixed and stirred, the temperature of the reaction system is increased to 70-80°C, an initiator solution is added dropwise to the reaction system, the reaction is kept warm for 6-7 hours, and post-processed to obtain polyacrylate; The preparation method of the polyurethane emulsion is as follows: under the protection of inert gas, polytetramethylene glycol, trimethylolpropane, hydroxy silicone oil and a catalyst are mixed and stirred, the temperature of the reaction system is increased to 70-80°C, isophorone diisocyanate is added dropwise to the reaction system, the reaction is kept warm for 2-3 hours, 2,2-dimethylolpropionic acid is added to the reaction system, the reaction is kept warm for 2-3 hours, triethylamine is added to the reaction system, the pH of the system is adjusted to 7, deionized water is added to the reaction system, emulsification and dispersion are performed, and the polyurethane emulsion is obtained; S2, adding the composite polyurethane, modified graphene and emulsion into a high-speed disperser, emulsifying and dispersing for 20-30 minutes to obtain a water-based coating premix; Wherein, the modified graphene is processed by the following steps: Under the protection of inert gas, graphene oxide and N,N-dimethylformamide are mixed, ultrasonically dispersed at room temperature for 30-50 minutes, N,N'-dicyclohexylcarboximide is added to the reaction system, and ultrasonication is carried out for 20-30 minutes at a temperature of 65-75°C. N,N-dimethylethylenediamine is added to the reaction system, and the reaction is carried out at a temperature of 20-22 hours, and post-processed to obtain a modified graphene precursor; The modified graphene precursor and dimethyl sulfoxide are mixed, ultrasonically dispersed for 40-60 minutes, the temperature of the reaction system is increased to 60-70° C., butyl bromide is added to the reaction system, the reaction is kept warm for 8-10 hours, and post-processed to obtain modified graphene; S3. Cool the water-based paint premix to 10-15° C., add KH-560 and additives to the water-based paint premix, and stir for 3-5 minutes to obtain a water-based paint.

2. The method for preparing a water-based coating for antistatic treatment of flexible PVC materials according to claim 1, characterized in that: In step S1, the usage ratio of the polyacrylate and the polyurethane emulsion is 1 g:10 mL, and the concentration of the sodium hydroxide solution is 1-2 mol / L.

3. The method for preparing a water-based coating for antistatic treatment of flexible PVC materials according to claim 1, characterized in that: In step S2, the amount ratio of the composite polyurethane, modified graphene and emulsion is 5g:1g:20mL, the emulsion is composed of sodium dodecylbenzene sulfonate, Tween-80, sodium hydroxide and deionized water in a ratio of 3g:2g:1g:100mL, and the rotation speed of the high-speed disperser is 1000-1200r / min.

4. The method for preparing a water-based coating for antistatic treatment of flexible PVC materials according to claim 1, characterized in that: In step S3, the amount ratio of the water-based paint premix, KH-560 and the additive is 100mL:3g:8g, and the additive consists of a thickener, an anti-settling agent, an anti-mildew agent, and a leveling agent in a weight ratio of 6:2:3:

2. The thickener is hydroxyethyl cellulose, the anti-settling agent is fumed silica, the anti-mildew agent is 2-(4-thiazolyl)benzimidazole, and the leveling agent is an acrylic leveling agent.

5. The method for preparing a water-based coating for antistatic treatment of flexible PVC materials according to claim 1, characterized in that: The dosage ratio of the methyl methacrylate, butyl acrylate, acrylic acid, 1,2-epoxy-7-octene, n-butanol and the initiator solution is 5g:3g:3g:2g:50mL:10mL, and the initiator solution is composed of azobisisobutyronitrile and n-butanol in a ratio of 1g:20mL.

6. The method for preparing a water-based coating for antistatic treatment of flexible PVC materials according to claim 1, characterized in that: The dosage ratio of the polytetramethylene glycol, trimethylolpropane, hydroxy silicone oil, catalyst and deionized water is 5g:1g:3g:0.1g:30mL, the isophorone diisocyanate is calculated according to N(OH):N(NCO)=1mol:1.1mol in the reaction system, and the molar amount of the 2,2-dimethylolpropionic acid is 0.05 times the molar amount of isophorone diisocyanate.

7. The method for preparing a water-based coating for antistatic treatment of flexible PVC materials according to claim 1, characterized in that: The usage ratio of the graphene oxide, N,N-dimethylformamide, N,N'-dicyclohexylcarbocyanine and N,N-dimethylethylenediamine is 1g:200mL:1.2g:3g; the usage ratio of the modified graphene precursor, dimethyl sulfoxide and butyl bromide is 1g:100mL:4g.

Citation Information

Patent Citations

  • Transparent antistatic coating on basis of graphene materials, antistatic functional membrane and method for preparing same

    CN106519947A

  • Polyurethane modified thermal insulation coating and preparation method thereof

    CN111154356A